BOOK REVIEW: AFRICAN HERMENEUTICS - W. Wessels (Acta Theologica)
Mburu, E. (HippoBooks, ACTS and Langham Publishing, 2019), 252 pp. Price: R500 (paperback) ISBN: 978-1-78368-464-9 is reviewed by W. Wessels.